2022
DOI: 10.1093/narcan/zcac010
|View full text |Cite
|
Sign up to set email alerts
|

A m6Avalue predictive of prostate cancer stemness, tumor immune landscape and immunotherapy response

Abstract: The molecular mechanisms underpinning prostate cancer (PCa) progression are incompletely understood, and precise stratification of aggressive primary PCa (pri-PCa) from indolent ones poses a major clinical challenge. Here, we comprehensively dissect, genomically and transcriptomically, the m6A (N6-methyladenosine) pathway as a whole in PCa. Expression, but not the genomic alteration, repertoire of the full set of 24 m6A regulators at the population level successfully stratifies pri-PCa into three m6A clusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 79 publications
4
9
0
Order By: Relevance
“…Increasing studies have revealed the m 6 A regulatory patterns of PCa and correlated these modification patterns with the tumor immune cell infiltration microenvironment characteristics ( 49 51 ). In addition, a recent paper found that m 6 A reader HNRNPC can regulate Treg cell abundance as a possible mechanism for m 6 A methylation-mediated response against CTLA-4, indicating that activation of the immune microenvironment by targeting m 6 A regulators may serve as a potential therapeutic approach for advanced PCa( 52 ).Our study synthetically analyzed the relationship between the expression of m 6 A regulators and immune characteristics and drug sensitivity of PCa patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have revealed the m 6 A regulatory patterns of PCa and correlated these modification patterns with the tumor immune cell infiltration microenvironment characteristics ( 49 51 ). In addition, a recent paper found that m 6 A reader HNRNPC can regulate Treg cell abundance as a possible mechanism for m 6 A methylation-mediated response against CTLA-4, indicating that activation of the immune microenvironment by targeting m 6 A regulators may serve as a potential therapeutic approach for advanced PCa( 52 ).Our study synthetically analyzed the relationship between the expression of m 6 A regulators and immune characteristics and drug sensitivity of PCa patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zou et al. proposed that PCa patients with low m6Avalues respond better to immunotherapy and had a longer survival time ( 29 ). Consistently, our results indicated that the CRPGS was positively associated with m6Avalue, and low-risk PCa patients had lower m6Avalues and m6Alevels, which implied that low-risk patients exhibited lower levels of m6A status and had a better response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The established CRPGS was compared with our two previously published PCa signatures ( 16 , 24 ) and another five PCa molecular classifiers to evaluate the wide application of CRPGS ( 25 29 ), which was described in the Supplementary Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Zou et al. [84]. divided PCa into three groups with distinct molecular and clinical characteristics according to the expression profile of m6A regulators, and established an m6A value based on the scoring characteristics of m6A phenotype‐related genes to quantify m6A modifications in individual PCa patient pattern.…”
Section: Introductionmentioning
confidence: 99%